Нigh-current ion beam compensation in a section of an induction linac - Karas’, V.I.; Kornilov, E.A.; Manuilenko, O.V.; Tarakanov, V.P.; Fedorovskaya, O.V. (Вопросы атомной науки и техники, 2018)
The particle transport dynamics in the section of a linear induction accelerator (LIA) has been studied. The system and beams parameters (the magnetic field magnitude, the system dimensions, the beams parameters), which
allowed compensating the ion beam in the entire LIA section are found. It is shown, that the high-current ion beam
(HCIB) at the system output can be used in many technological applications. Досліджена динаміка транспортування часток у секції лінійного індукційного прискорювача (ЛІП).
Знайдено параметри системи і пучків (величина магнітного поля, розміри системи), при яких здійснюється
компенсація іонного пучка вздовж всієї секції ЛІП. Показано, що іонний пучок на виході з системи може
бути використаний в багатьох технологічних додатках. Изучена динамика транспортировки частиц в секции линейного индукционного ускорителя (ЛИУ).
Найдены параметры системы и пучков (величина магнитного поля, размеры системы), при которых осуществляется компенсация ионного пучка вдоль всей секции ЛИУ. Показано, что ионный пучок на выходе из
системы может быть использован во многих технологических приложениях.